Adaptation of three oral expression techniques in virtual classes - López Montero, Rosberly (2026)
The objective of this essay is to reveal the adaptation of three oral expression techniques to virtual classes: the individual exposition, the debate and the cineforum.  Every technique’s adaptation is detailed in three parts: planning, platform and proposal. It is concluded that, even though the sudden change to virtual learning due to COVID-19 represented a challenge for the development of the oral expression in the classroom, the use of new technological tools allows for the improvement of the oral expression to continue evolving in those scenarios in which those tools are available.